Technical Lignins Antibacterial Effects Against Environmental Mastitis Pathogens Across Various Levels of Bedding Cleanliness In Vitro - Godloves M. Oppong; Diana C. Reyes; Zhengxin Ma; Santiago A. Rivera; Marjorie A. Killerby; Diego Zamudio; Anne B. Lichtenwalner; Juan J. Romero (Molecules, 2025)
This study aimed to evaluate the antibacterial activity of several technical lignins against major environmental bacteria that cause mastitis in dairy cattle. The efficacy of four types of technical lignins against environmental mastitis pathogens was evaluated using MIC and MBC assays. The best candidate, sodium lignosulfonate (NaL-O), was further tested using sawdust bedding substrates. Substrates were prepared in different cleanliness conditions: sawdust only, sawdust plus urine, sawdust plus feces, or sawdust plus a combination of both. The antimicrobial activity of NaL-O against the mixture of environmental mastitis-causing pathogens was determined on days 0, 2, and 6 of incubation. In addition, the components of bedding substrates were analyzed to help understand the dynamics of pathogen loads. In the MIC and MBC assays, NaL-O showed the best antimicrobial performance against all pathogens except Escherichia coli. When testing in the bedding substrates, the addition of NaL-O decreased the concentration of Staphylococcus chromogenes, Streptococcus uberis, and Pseudomonas aeruginosa across all bedding cleanliness levels at d 0, 2, and 6 of incubation. As the incubation time increased, the antimicrobial effect decreased. NaL-O also lowered the counts of E. coli and Klebsiella pneumoniae across all incubation times, but to a lesser extent. The presence of feces significantly reduced the antibacterial effects of NaL-O for these two bacteria. Among the technical lignins tested, NaL-O showed the broadest antibacterial activity against the mastitis pathogens tested. This study suggests that NaL-O has promising potential as a bedding conditioner to control environmental pathogens on dairies due to its low cost, ready availability, and compatibility with sustainable livestock practices. Combined with bedding cleanliness, bedding conditioner application may play a crucial role in reducing the growth of EM pathogens and subsequent mastitis incidence.